Oscillation and Dynamic Instability of Ships Fin Stabilizer (University of Thi-Qar Journal for Engineering Sciences, 2022)
Ships are considered one of the most important means of transportation in the world, especially at the present time, These ships are exposed to harsh climatic conditions, and The loss of people and cargo, as well as the loss of ships, are all repercussions of these situations. In this research, the fin with the flap was studied practically, and the aim of it is to study several angles of the flap to achieve the best balance for ships at several speeds. Where the fin was made according to the international standard NACA 0015, with a length of 30 (cm) and a width of 13 (cm) of aluminum alloy with a flap length of 4( cm) and a width of 14 (cm) of aluminum alloy as well. Where it was installed in a wind tunnel device with the fluid pressure applied to it and changing the angle of the flap to 9 angles, also using 5 speeds for each angle and calculating the vibration of the flap using the Vibration Meter device at each angle and for each speed It was found that the least vibration occurred at the angle of 15ͦ , so it is preferable to adopt this angle when designing the wing in order to balance the ship.